2015
DOI: 10.1186/s13099-015-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

The neurotoxic effects of ampicillin-associated gut bacterial imbalances compared to those of orally administered propionic acid in the etiology of persistent autistic features in rat pups: effects of various dietary regimens

Abstract: HypothesisA healthy gut with normal intestinal microflora is completely disrupted by oral antibiotics. The byproducts of harmful gut bacteria can interfere with brain development and may contribute to autism. Strategies to improve the gut microflora profile through dietary modification may help to alleviate gut disorders in autistic patients.MethodSixty young male western albino rats were divided into six equal groups. The first group served as the control; the second group was given an oral neurotoxic dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…It has been reported that the impact of antibiotics on the gut microbiome can be attributed to its antimicrobial spectrum and the antimicrobial activity in the colon depending on concentrations [ 46 , 47 ]. Previous studies examined the effect of several types of antibiotics on the perturbation of gut microbiota, which may lead to an alteration in colonic mucosal homeostasis and microbial metabolites [ 18 , 27 , 48 , 49 ]. Høverstad et al reported that considerably changed SCFA profiles were observed according to the administration of ampicillin (500 mg four times daily) in the human clinical trial [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the impact of antibiotics on the gut microbiome can be attributed to its antimicrobial spectrum and the antimicrobial activity in the colon depending on concentrations [ 46 , 47 ]. Previous studies examined the effect of several types of antibiotics on the perturbation of gut microbiota, which may lead to an alteration in colonic mucosal homeostasis and microbial metabolites [ 18 , 27 , 48 , 49 ]. Høverstad et al reported that considerably changed SCFA profiles were observed according to the administration of ampicillin (500 mg four times daily) in the human clinical trial [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 Several reports discuss clinical associations, biochemical testing, and therapeutic management of ASD cases in the Saudi population, but very few reports have been published regarding genetic variations in this population. [2][3][4][5] Due to increasing prevalence, ASD brings substantial economic and emotional burdens to affected families and societies. 6 Genetic and environmental factors may play a substantial role in the development of ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the gut flora can induce oxidative stress which in turn can increase the neurotoxic effect of the drug and can remarkably affects the brain in rodent models of autism 12 . Several recent studies have shown that dietary factors alter the microbial community resulting in biological changes to the host and overall, dietary changes could explain 57% of the total structural variation in gut microbiota whereas changes in genetics accounted for no more than 12% 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Ampicillin-induced neurotoxicity has also been described in the literature in very low birth weight neonates 11 . A recent study by El-Ansary 12 has shown ampicillininduced neurotoxicity that might induce autistic traits in animal model of autism.…”
mentioning
confidence: 99%